PENERTIBAN SINDEN PADA PERTUNJUKAN WAYANG GOLEK: KERESAHAN BAGI DALANG DI JAWA BARAT - S.Sn., M.Sn., Masyuning (LP2M ISBI Bandung, 2018)
This paper presented sind n as part of the wayang gol k show in West Java. Before the G30S/PKI incident sind n was so popular, it even beat the popularity of the dalang. This phenomenon caused unrest for the dalang in West Java. The government intervened to curb the sind n which was seen as too wild. The incident of sind n which caused unrest stopped after a seminar padalangan was held in1964. This event proved that the comunity of Padalangan were able to unite to solve that problem.